WEB-BASED PREGNANT WOMEN'S HEALTH RECORDING INFORMATION SYSTEM - Suryadi, Agung; Khoiriyah, Dakwatul; Fernandes, Irene; Xavier, Pascoela da C. de Jesus (LPPM Universitas Duta Bangsa Surakarta, 2025)
Integrated Health Posts are basic health services for pregnant women. Currently, services at Posyandu, including registration and recording of examination results, are still performed manually, written in a maternity register. This makes data processing difficult and reports inaccurate. This research aims to design a website-based information system to assist cadres and midwives in more efficient registration, recording, data processing, and reporting. This research is a descriptive study with observation and interview data collection methods using a cross-sectional approach. The subjects in this study were village midwives and cadres, while the object of this research was the flow of recording and processing data on pregnant women. The method used was the development of the System Development Life Cycle (SDLC), which is the process of designing and creating a system, as well as the methodology used to develop the system. The website-based maternal health information system was developed using the PHP programming language and MySQL database. The resulting output is a report on the processing of pregnant women, as well as examinations and immunization data. The results of this study indicate that the application of the developed information system can facilitate staff in registering, recording, processing, and reporting, thus providing optimal pregnancy registration services.